Vitamin C for the Prevention of Postoperative Atrial Fibrillation after Cardiac Surgery: A Meta-Analysis - Evangelos Polymeropoulos; Pantelis Bagos; Maria Papadimitriou; Ioannis Rizos; Efstratios Patsouris; Ioannis Toumpoulis (Tabriz University of Medical Sciences, 2016)
Purpose: Several studies have investigated the administration of vitamin C (vitC) for the prevention of postoperative atrial fibrillation (AF) after cardiac surgery. However, their findings were inconsistent. The purpose of this meta-analysis was to evaluate the efficacy of vitC as prophylaxis for the prevention of postoperative AF in cardiac surgery. Methods: A systematic search of PubMed, EMBASE, Google Scholar, the Cochrane Library, and clinical trial registries, was performed. 9 studies, published from August 2001 to May 2015, were included, with a total of 1,037 patients. Patients were randomized to receive vitC, or placebo. Results: Cardiac surgery patients who received vitC as prophylaxis, had a significantly lower incidence of postoperative AF (random effects OR=0.478, 95% CI 0.340 - 0.673, P < 10-4). No significant heterogeneity was detected across the analyzed studies (I2=21.7%), and no publication bias or other small study-related bias was found. Conclusion: Our findings suggest that VitC is effective as prophylaxis for the prevention of postoperative AF. The administration of vitC may be considered in all patients undergoing cardiac surgery.